Prioritization preferences for COVID-19 vaccination are consistent across five countries - Munzert, Simon; Ramirez-Ruiz, Sebastian; Çalı, Başak; Stoetzer, Lukas F.; Gohdes, Anita; Lowe, Will (Humanities and Social Sciences Communications, 2022)
Vaccination against COVID-19 is making progress globally, but vaccine doses remain a rare commodity in many parts of the world. New virus variants require vaccines to be updated, hampering the availability of effective vaccines. Policymakers have defined criteria to regulate who gets priority access to the vaccination, such as age, health complications, or those who hold system-relevant jobs. But how does the public think about vaccine allocation? To explore those preferences, we surveyed respondents in Brazil, Germany, Italy, Poland, and the United States from September to December of 2020 using ranking and forced-choice tasks. We find that public preferences are consistent with expert guidelines prioritizing health-care workers and people with medical preconditions. However, the public also considers those signing up early for vaccination and citizens of the country to be more deserving than later-comers and non-citizens. These results hold across measures, countries, and socio-demographic subgroups.
CRIS-Team Scopus Importer:2024-06-28